Penelantaran, Perceraian, dan Perkawinan Lintas Agama: Analisis Hukum Islam Dan Studi Putusan PA Nomor 2871 Medan 2023 - Mukhlis Siregar; Tanjung, Dhiauddin; Siregar, Ramadhan Syahmedi (Empirisma: Jurnal Pemikiran dan Kebudayaan Islam, 2025)
This study aims to analyze the legal basis employed by the judge in deciding a divorce case due to neglect, as outlined in the Decision of the Religious Court of Medan No. 2871 of 2023. The research adopts a normative juridical method with statutory and case approaches. The data sources include applicable legal regulations and an analysis of the judicial decision. The findings reveal that the judge based the ruling on Article 19 of Government Regulation No. 9 of 1975 in conjunction with Article 116 of the Compilation of Islamic Law (KHI) of 1991, which stipulate that abandonment for a consecutive period of two years constitutes a valid ground for divorce. Additionally, the judge referred to Article 82 paragraph (4) of Law No. 7 of 1989 as amended by Law No. 50 of 2009, which permits a verstek (default) judgment when the defendant fails to appear despite having been duly summoned. The judicial decision in this case is considered to be in accordance with both Islamic legal principles and the positive law in Indonesia, taking into account justice for the plaintiff, particularly in matters of child custody and the obligation of financial support for the former wife and children. This study affirms that neglect within marriage constitutes a violation of spousal obligations that has legal consequences for the abandoned party. The findings are expected to contribute to the development of family law, particularly regarding the implementation of statutory provisions in divorce cases arising from spousal neglect.